The use of interferon in medicine - Waldemar Pluta; Wioleta Dudzińska; Anna Lubkowska (Kazimierz Wielki University, 2020)
Interferons are low-molecular weight glycoproteins. They are characterized by paracrine and autocrine activity. Their production and release occurs through various types of cells, which ultimately leads to the protection of the body against viral infections. Interferons do not have direct antiviral activity but affect cells, inducing the formation of antiviral agents and "antiviral readiness" in them. Thanks to their properties interferons have been widely used in the treatment of many diseases, among others hepatitis B, hepatitis C and multiple sclerosis. In addition, they show anti-cancer effects, even in the case of chronic myeloid leukemia. They are currently an important element in the search for a drug against SARS-CoV-2.